Cytokine signaling converging on IL11 in ILD fibroblasts provokes aberrant epithelial differentiation signatures - Kastlmeier, Miriam T.; Gonzalez-Rodriguez, Erika; Cabanis, Phoebe; Guenther, Eva M.; König, Ann-Christine; Han, Lianyong; Hauck, Stefanie M.; See, Fenja; Asgharpour, Sara; Bukas, Christina; Burgstaller, Gerald; Piraud, Marie; et al. (Frontiers in Immunology, 2023)
Interstitial lung disease (ILD) is a heterogenous group of lung disorders where destruction and incomplete regeneration of the lung parenchyma often results in persistent architectural distortion of the pulmonary scaffold. Continuous mesenchyme-centered, disease-relevant signaling likely initiates and perpetuates the fibrotic remodeling process, specifically targeting the epithelial cell compartment, thereby destroying the gas exchange area. With the aim of identifying functionally relevant mediators of the lung mesenchymal-epithelial crosstalk that hold potential as new targets for therapeutic strategies, we developed a 3D organoid co-culture model based on human induced pluripotent stem cell-derived alveolar epithelial type 2 cells that form alveolar organoids in presence of lung fibroblasts from ILD patients as well as a control cell line (IMR-90). While organoid formation capacity and size was comparable in the presence of ILD or control lung fibroblasts, metabolic activity was significantly increased in ILD co-cultures. Alveolar organoids cultured with ILD fibroblasts further demonstrated reduced stem cell function as reflected by reduced Surfactant Protein C gene expression together with an aberrant basaloid-prone differentiation program indicated by elevated Cadherin 2, Bone Morphogenic Protein 4 and Vimentin transcription. In order to screen for key mediators of the misguided mesenchymal-to-epithelial crosstalk with a focus on disease-relevant inflammatory processes, we used mass spectrometry and characterized the secretome of end stage ILD lung fibroblasts in comparison to non-chronic lung disease (CLD) patient fibroblasts. Out of the over 2000 proteins detected by this experimental approach, 47 proteins were differentially abundant comparing ILD and non-CLD fibroblast secretome. The ILD secretome profile was dominated by chemokines, including CXCL1, CXCL3, and CXCL8, interfering with growth factor signaling orchestrated by Interleukin 11 (IL11), steering fibrogenic cell-cell communication, and proteins regulating extracellular matrix remodeling including epithelial-to-mesenchymal transition. When in turn treating alveolar organoids with IL11, we recapitulated the co-culture results obtained with primary ILD fibroblasts including changes in metabolic activity. In summary, we identified mediators likely contributing to the disease-perpetuating mesenchymal-to-epithelial crosstalk in ILD. In our alveolar organoid co-cultures, we were able to highlight the importance of fibroblast-initiated aberrant epithelial differentiation and confirmed IL11 as a key player in ILD pathogenesis by unbiased ILD fibroblast secretome analysis.